Score calibration in face recognition. Issue 4 (1st December 2014) - Mandasari, Miranti Indar; Günther, Manuel; Wallace, Roy; Saeidi, Rahim; Marcel, Sébastien; van Leeuwen, David A.
Abstract : An evaluation of the verification and calibration performance of a face recognition system based on inter‐session variability modelling is presented. As an extension to calibration through linear transformation of scores, categorical calibration is introduced as a way to include additional information about images for calibration. The cost of likelihood ratio, which is a well‐known measure in the speaker recognition field, is used as a calibration performance metric. The results obtained from the challenging mobile biometrics and surveillance camera face databases indicate that linearly calibrated face recognition scores are less misleading in their likelihood ratio interpretation than uncalibrated scores. In addition, the categorical calibration experiments show that calibration can be used not only to improve the likelihood ratio interpretation of scores, but also to improve the verification performance of a face recognition system.